Implementation of Nanogrids for Future Power System - Amin, Uzma; Ahmed, Manzar; Aftab Qureshi, S; Ahmed, Z (2014)
Microgrid is a new technology in power generation and this system is used to provide power and heat to its local area, such as cogeneration systems and renewable energy (wind turbines, photovoltaic cells, etc.). They are preferred for medium or high power applications. Nanogrid most likely to be used in small local loads for rural area as they will be more economic then the normal grid power system. Nano grids can operate independently or be connected to the mains and most likely the internal voltage can be utilized as ac or dc. In this research paper a small scale microgrid system is proposed for smart homes called "Nanogrid". Each houses have small electrical power system from them can be shared among houses. If it uses a DC system instead of a general AC system, it can reduce energy loss of inverter because each generator doesn’t need an inverter. Furthermore, it can continue to provide a power supply when blackout occurs in the bulk power system. A model of a nanogrid is developed to simulate the operation of the centralized power control. Finally a Simulink model is presented for small houses power range 90-285 KW.